Perfomance of Chromium-Exchanged Zeolite Catalysts in the Combustion of Volatile Organic Compound Pollutants - Ahmad Zuhairi Abdullah; Mohamad Zallani Abu Bakar; Subhash Bhatia (ASEAN Journal of Chemical Engineering, 2004)
The activity and stability of chromium-exchanged beta (Cr-BEA),mordenite (Cr-MOR), and ZSM-5 (Cr-ZSM-5) zeolites of different Si/Alratios for volatile organic compounds (VOCS) combustion were reported. A fixed-bed catalytic reactor operated between 100 and 500°C and at a gas hourly space velocity (GHSV) of 32,000 h'! was used for the study. Methanol, ethyl acetate, methyl ethyl ketone, benzene, hexane, toluene, and xylene, all at 2,000 ppm, were selected as the VOC model compounds. Oxygenated VOCs were more reactive while showing good carton dioxide yield. Aromatics were more stable due to their resonance effect but the reactivity increased with the attachment of an electron donor group such as the methyl group. Cr-ZSM- 5(240) demonstrated the highest hydrothermal stability due to its high Si/Al ratio. Despite giving a high initial activity due to its high metal loading, Cr-BEA(25) was susceptible to coking in the long run. The high coke formation in mordenite and beta zeolites was attributed to their high acidity, interconnecting channels of different sizes, and relatively larger pore sizes. The coke that formed on Cr-ZSM-5(240) was more carbonaceous and oxidized at higher temperatures.